The Bavarian Illuminati and the Construction of the Masonic Conspiracy in Enlightenment Europe (1776–1792) - del Solar, Felipe Santiago (2025)
This paper analyzes how the scandal triggered by the discovery of the Bavarian Illuminati (Illuminatenorden) in Germany laid the foundation for the Masonic conspiracy theory that spread across Europe between 1776 and 1792. Through a critical review of printed sources, it explores how the Illuminati opposed mystical currents within Freemasonry and the Jesuits, developing a rationalist narrative. The article also examines how this internal conflict was projected into France through figures like Mirabeau and Bonneville, and how the resulting discourse eventually became a model for later conspiracy theories that linked Freemasonry to political subversion and anti-Enlightenment agendas.